Enhancing success in South Africa’s higher education: measuring student engagement - Strydom, Francois; Kuh, George; Mentz, Melody (Acta Academica: Critical views on society, culture and politics, 2010)
Improving student success and throughput rates are key challenges facing South African higher education. International research shows that a focus on student engagement can help to enhance student learning and other desired outcomes as well as the efficiency and effectiveness of higher education systems. This article documents the psychometric properties of the South African Survey of Student Engagement (SASSE), providing a sound basis on which to promote large-scale studies of student engagement-related interventions. Using this contextualised measure will allow South African institutions to engage in national and international benchmarking with countries such as the USA, Canada and Australia.